2007
DOI: 10.7863/jum.2007.26.2.215
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Temperature Estimation Using Sonographic Digital Images

Abstract: The proposed method verifies the capability of the speckle-tracking algorithm for determining both the magnitude and direction of displacement. The average error was 0.2 degrees C; the maximum error was 0.53 degrees C; and the SD was 0.19 degrees C. Therefore, the proposed algorithm is capable of extracting the temperature information from sonographic digital images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 20 publications
0
25
0
1
Order By: Relevance
“…Adolhassani and colleagues reported that isotropic speckle-tracking kernels from 2 mm to 4 mm had similar performance when maximum normalization cross-correlation was applied to B-mode images (75). In later work, Mehrabani et al utilized the Horn-Shunck method for visualizing optical flow to estimate the speckle displacement (76).…”
Section: Specific Strategies For Ultrasound Thermometry and Ablatimentioning
confidence: 99%
“…Adolhassani and colleagues reported that isotropic speckle-tracking kernels from 2 mm to 4 mm had similar performance when maximum normalization cross-correlation was applied to B-mode images (75). In later work, Mehrabani et al utilized the Horn-Shunck method for visualizing optical flow to estimate the speckle displacement (76).…”
Section: Specific Strategies For Ultrasound Thermometry and Ablatimentioning
confidence: 99%
“…For a therapeutic beam with a depth of focus on the order of 1–2 mm, unpredictable expansion and displacement of the acoustic focus would be significant. Moreover, while sound speed decreases in fat with increasing temperature, sound speed increases with temperature in most other tissues [16], [24]. Therefore, previous ultrasonic thermometry studies have created temperature maps by assuming a homogenous tissue and constant sound speed [14], [25].…”
Section: Discussionmentioning
confidence: 99%
“…Many previous techniques [13][14][15][16][17][18][19] rely on a beam-formed amplitude contrast image and correlation methods to determine the temperature change. These techniques can be easily corrupted by speckle noise, an effect which does not directly represent a physical feature in the region of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Under this assumption, an increase in temperature will shift the image, and by comparing the apparent spatial shift with an initial ͑un-heated͒ image, the sound speed change can be determined. [13][14][15][16][17][18][19] A second phenomenon which will occur is thermal expansion, which results in a physical shift in the tissue. 9,[11][12][13]19 Seip and Ebbini 10 used the spectrum of the measured backscattered rf signal to track heating.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation